Analisa Faktor-Faktor Penyebab Gangguan Jiwa Menggunakan Pendekatan Model Adaptasi Stres Stuart - Fajar Rinawati; Moh Alimansur (coba, 2016)
Mental disorder can occus in all people, either children, adults or elderly. Mental disorder also can occurs anywhere, either people that living in cities or villages. The caused of mental disorder derived from biological, psychological and social aspects. The purpose of this study was to determine the factors that caused mental disorder. The methodology of this study was quantitative descriptive using purposive sampling for 9 weeks. The sample of this study was 46 respondents. The results showed that the most predispocing factor was the client ever experienced previous mental disorder before, personality type and unemployment client, and the most precipitation factor was withdrawal, an unpleasant experience and conflicts with family and friends. Based on the results of this study expected that the nursing intervention for client with mental disorder not only treating the signs and symtoms but also preventing mental disorder to overcome/reduce the factors. Keywords: mental disorder, etyology, and analysis of factor